Pyrazine analogues from wolf urine induced unlearned fear in rats - Kashiwayanagi, Makoto (Heliyon, 2017)
Urine excreted from the common grey wolf (Canis lupus) contains a kairomone, inducing fear-related behaviors in various mammals. Numerous fear-inducing substances activate neurons at the main and/or accessory olfactory bulb (AOB), medial and central amygdala, and hypothalamus. Our previous study showed that the mixture of pyrazine analogues (P-mix) contained in wolf urine induced avoidance and fear-related behaviors in laboratory mice and Hokkaido deer (Cervus nippon yesoensis), a species native to Japan. Exposure to wolf urine or P-mix induced expression of Fos, a marker of neuronal excitation, in the AOB of mice. In the present study, we explored the effects of P-mix on fear-related behaviors and Fos-expression in rats. Exposure to P-mix induced avoidance and immobilization in rats, while that to a mixture of i-amyl acetate, linalool and R(+)-limonene (O-mix), which generate floral and fruity odors, induced avoidance but not immobilization. P-mix but not O-mix increased Fos-immunoreactivity of the AOB, medial and central amygdala, and hypothalamus of rats. The present results suggest that P-mix odor induces unlearned fear-related behaviors in rats.